Інтерактивні форми політичної комунікації - Вайєр, Аліна Марленівна; Вайєр, А. М.; Вайер, Алина Марленовна; Vaiier, Alina M. (Одеса : Фенікс, 2019)
В Інтернеті як сформованому політичному інституті традиційна структура подачі семантичної інформації видозмінюється. Оскільки інформатизація і демократизація української держави є актуальним політичним завданням, простір інтернет-комунікацій стає ареною для вироблення консолідованої політичної позиції влади і суспільства. Комунікаційні особливості Інтернету дозволяють здійснювати легітимний політичний дискурс суспільства з владою. В даній статті розглянуто відмінності політичної комунікації від звичайної, проаналізовано різні моделі політичної комунікації, також проведен аналіз функцій політичної комунікації на прикладі досліджень інших вчених. Взагалі, кількість Інтернет-користувачів постійно зростає протягом багатьох років, серед них більше молодих і освічених соціальних груп. І саме для молоді та людей, які мають потреби у підвищенні свого освітнього рівня, Інтернет стає важливим джерелом отримання інформації і знань. Важливо також і те, що з розвитком інтернет-спільнот і розвитку в них об’ємного фонового по відношенню до політичного життя середовища, традиційні способи комунікації політики з електоратом втрачають ефективність, а рівень довіри політичної інформації з офіційних джерел падає. А віртуальність, як штучно створений світ, де людина має спілкуватися не з речами, а з їх образами, дає широкі можливості для пошуків нових методів політичного впливу. І все ж таки робиться висновок, що у контексті сучасної української дійсності, політична комунікація, виступаючи засобом існування і трансляції політичної культури, в свою чергу, може стати фундаментом демократизації взаємодії держави і громадянського суспільства.

В Интернете как сформированном политическом институте традиционная структура подачи семантической информации видоизменяется. Поскольку информатизация и демократизация украинского государства является актуальным политическим заданием, пространство интернет-коммуникаций становится ареной для выработки консолидированной политической позиции власти и общества. Коммуникационные особенности Интернета позволяют осуществлять легитимный политический дискурс общества с властью. В данной статье рассмотрены различия политической коммуникации от обычной, проанализированы различные модели политической коммуникации, также проведен анализ функций политической коммуникации на примере исследований других ученых. Вообще, количество Интернет-пользователей постоянно растет на протяжении многих лет, среди них все более молодые и образованные социальные группы. И именно для молодежи и людей, которые нуждаются в повышении своего образовательного уровня, Интернет становится важным источником получения информации и знаний. Важно также и то, что с развитием интернет-сообществ и развития в них объемной фоновой по отношению к политической жизни среды, традиционные способы коммуникации политики с электоратом теряют эффективность, а уровень доверия политической информации из официальных источников падает. А виртуальность, как искусственно созданный мир, где человек должен общаться не с вещами, а с их образами, дает широкие возможности для поисков новых методов политического влияния. И все же делается вывод, что в контексте современной украинской действительности, политическая коммуникация, выступая средством существования и трансляции политической культуры, в свою очередь, может стать фундаментом демократизации взаимодействия государства и гражданского общества.

On the Internet, as a formed political institute, the traditional structure of semantic information submission is changing. As informatization and democratization of the Ukrainian state is an urgent political task, the space of Internet communications becomes an arena for developing a consolidated political position of the authorities and society. The communication features of the Internet make it possible to exercise a legitimate political discourse on society with the authorities. It is possible to update the political communication of the state as follows: to digitize the power management process, to put into practice “e-government” and “e-democracy”, to use Internet technologies by managers and officials at all levels, to increase computer literacy of the population. This article examines the differences between political and ordinary communication, analyzes various models of political communication, and analyzes the functions of political communication on the example of research by other scholars, and the conclusion is made that in the context of modern Ukrainian reality, political communication, both, livelihood and broadcast political culture, in turn, can become the foundation of democratic interaction of the state and civil society. Internet modified traditional political institutions formed the structure of supply semantic information. As the informatization and democratization of the Ukrainian state is relevant, the space of Internet communications becomes an arena for developing a consolidated political position of the authorities and society. The communication features of the Internet make it possible to exercise a legitimate political discourse on society with the authorities. In general, the number of Internet users has been steadily increasing over the years, including more young and educated social groups. It is for young people and people who need to improve their educational level that the Internet becomes an important source of information and knowledge. It is also important that with the development of online communities and the development of voluminous backgrounds with respect to the political life of the environment, traditional ways of communicating politics with the electorate are losing effectiveness, and the level of trust in olitical information from official sources is falling. And virtuality, as an artificially created world where one has to communicate not with things but with their images, provides ample opportunity for finding new methods of political influence .
Вайєр А. М. Інтерактивні форми політичної комунікації / А. М. Вайєр // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. редкол.), Л. І. Кормич (голов. ред.), І. М. Милосердна (відп. ред.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Фенікс, 2019. – Вип. 64. – С. 134-144.
Keywords: політична комунікація; інтерактивність; політична свідомість; Інтернет; соціальні мережі; политическая коммуникация; интерактивность; политическое сознание; Интернет; социальные сети; political communication; interactivity; political consciousness; Internet; social networks; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science